Ethics for fundraisers - Anderson, Albert, 1928- (Philanthropic studies., 1996)
"Invoking a variety of classical and contemporary models, Albert Anderson examines what it means to think and act ethically. Proceeding from the views of Immanuel Kant and John Stuart Mill - who created perhaps the two most influential, albeit competing, ethical frameworks - Anderson poses the choice between what we understand to be our moral duty and what will likely result in the greatest good for the majority. He applies these notions to a wide range of situations familiar to nonprofit development officers, volunteers, and organizations. His goal is to help readers rethink decision-making and the principles that guide their decisions. To clarify and test these principles, Anderson presents a hypothetical case and concludes with a program for developing and refining (through experience) a code of ethics for the organization."--Jacket